IS SHARIA MORTGAGE REALLY USURY-FREE? A CRITICAL REVIEW OF THE THREE MAZHAB OF ISLAMIC ECONOMICS - Awaliyah, Siti Uswatun; Artanti, Sazkhia; Yulianti, Alifia Hanin; Mukti, Titania (Journal of Management and Islamic Finance, 2025)
Sharia Home Ownership Loans (KPR) are an alternative for Muslims to own a house without the practice of usury. Unlike conventional interest-based mortgages, Islamic mortgages use muamalah contracts such as murabahah, istishna', ijarah muntahiyah bit tamlik, and musyarakah mutanaqisah. However, the similarity of the payment structure with conventional mortgages has led to criticism of its sharia validity. Thtis research uses a qualitative-descriptive approach through literature studies and case studies on three Islamic mortgage products in Indonesia. The analysis was conducted using a fiqhiyyah approach and reviewed from three madhhab of Islamic economic thought. The results show that despite fulfilling the formal provisions of sharia, substantively there is still debate. The development of Islamic mortgages needs to be directed towards achieving maqashid sharia and economic Keyword: Sharia Mortgage, Usury, Islamic Economics, Islamic Economic Madhhabs